Knowledge, attitudes, and practices on hemangioma among parents of infantile hemangioma patients in South China - Xiaoyun Tan; Zhenyin Liu; Haibo Li; Jiejun Xia; Chuanqiang Niu; Xiaoying Liu; Xiaotong Liang; Honglin Wang (Scientific Reports)
Abstract This study investigated the knowledge, attitudes, and practices (KAP) of parents of infantile hemangioma (IH) patients in South China through a cross-sectional survey conducted from November 2023 to March 2024. A structured questionnaire was administered to 511 participants, with 63.01% being female. The mean scores reflected inadequate knowledge (5 out of 9), generally positive attitudes (45 out of 55), and relatively inactive practices (24 out of 40). Direct effect analysis indicated that the number of consultations (β = 0.464, P = 0.012) and the presence of congenital vascular anomalies or metabolic disorders (β = 0.085, P = 0.029) positively influenced parental knowledge. Knowledge significantly affected attitudes (β = 0.509, P = 0.011), while both attitudes (β = 0.436, P = 0.018) and congenital conditions (β = − 0.189, P = 0.007) impacted practices. Additionally, consultations and congenital conditions indirectly influenced attitudes (β = 0.236, P = 0.012) and practices (β = 0.222, P = 0.011). The findings highlight the need for targeted educational interventions to enhance parental understanding and engagement in managing IH effectively.